FROZEN FOOD SALES SYSTEM AT DAKON STORE USING FRAMEWORK FOR THE APPLICATION SYSTEM THINKING METHOD - Mangli, Luh Ajeng Roro; Fajri, Ika Nur (ZONAsi: Jurnal Sistem Informasi, 2024)
Increasingly advanced information and communication technology has triggered various influences, including a significant need for the Internet. This technological development disrupts the business sector, especially trade, which requires a shift from conventional stores to online stores to accelerate and increase sales through e-commerce, which expands market share without limits. The Dakon frozen food shop, established in 2018, needs help with conventional sales, which force buyers to come to the shop, as well as time-consuming manual stock and sales data collection. To overcome this problem, the author proposes developing a website-based information system using the FAST (Framework for the Application of System Thinking) method, making it easier to design systems, analyze needs, and build appropriate systems. Implementing this system is expected to expand the reach of buyers, increase sales, and improve governance. With the FAST method, various operational challenges can be overcome more effectively. Payments have become more efficient through automation of the sales process, although improvements to the website's appearance are still needed to improve the user experience